Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Surat Kabar Suara Merdeka Di Kota Semarang - Fauzia Elva Putri; Sri Suryoko; Sendhang Nurseto (Universitas Diponegoro, 2015)
Newspaper is one of the frequently used means of information society. One of the newspapers of interest by people in Semarang with prices that are not too expensive and with a good quality of product is the newspaper Suara Merdeka. But with the advent of many competitors, the Suara Merdeka newspaper sales decline. Becouse of that, this research aim to determine the influence of quality product to purchasing decisions and the influence of price to purchasing decisions.The sampling technique used is Non-Probability Sampling and the sampling type used is Accidental Sampling. Sample in this research is 100 respondents consisting of Suara Merdeka consumers. Data analysis using analysis qualitative and quantitative with validity and reliability , simple regression analysis, double regression analysis, t test and f test with program spss 16.0 for windows.The results of research shows that there is a positive effect and significant between the product quality to purchasing decision amount 22,9 % and the price have positive effect and significant to purchasing decision amount 5.6 %.The price of Suara Merdeka worthy maintained becouse it is already adequate and not into consideration important for cunsumers to made the purchase. The quality of product needs to be considered balance is the aspect of the news, neatness as well as clarity mold.